A method for determining precise electrical hearing thresholds in cochlear implant users. (3rd July 2018) - Rader, Tobias; Doms, Philipp; Adel, Youssef; Weissgerber, Tobias; Strieth, Sebastian; Baumann, Uwe
Abstract: Objective : A psychoacoustic procedure designed for the precise assessment of perceptional threshold (T-level) in cochlear implant (CI) users is presented. The impact of this procedure on speech perception was investigated. Design : Individual T-level measurements were obtained with the proposed procedure and three different speech processor fitting conditions were applied: (1) fitting familiar to the subject, T-levels unchanged, (2) T-level set to thresholds determined with the new procedure, (3) T-level set to thresholds determined with the new procedure, but T-level is decreased by 10 clinical units (CU). The impact of the different fitting conditions was measured by means of categorical loudness scaling (CLS) and speech perception tests in quiet and noise. Study sample : A prospective study at a tertiary referral university hospital. 18 experienced postlingually deafened cochlear implanted adult subjects. Results : Average sound-field thresholds obtained by CLS were lowest in condition using the new procedure yielding a larger dynamic range with significantly higher speech scores in quiet compared to those with a subject's commonly used programme, and significantly improved in noise even after reducing T-levels by 10 CU. Conclusion : The precise determination of T-levels by means of the proposed procedure improved performance in several speech recognition tasks. Compared to the default behavioural setting, T-level increased on median by 9 CU. Average speech reception threshold in noise for soft speech levels (50 dB sound pressure level) decreased by 1 dB.